Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 195254 by Spillover last updated on 28/Jul/23

∫((sin^2 xcos^2 x)/((sin^5 x+cos^3 xsin^2 x+sin^3 xcos^2 x+cos^5 x)))dx

$$\int\frac{\mathrm{sin}\:^{\mathrm{2}} {x}\mathrm{cos}\:^{\mathrm{2}} {x}}{\left(\mathrm{sin}\:^{\mathrm{5}} {x}+\mathrm{cos}\:^{\mathrm{3}} {x}\mathrm{sin}\:^{\mathrm{2}} {x}+\mathrm{sin}\:^{\mathrm{3}} {x}\mathrm{cos}\:^{\mathrm{2}} {x}+\mathrm{cos}\:^{\mathrm{5}} {x}\right)}{dx} \\ $$

Commented by Frix last updated on 28/Jul/23

=∫((sin^2  x cos^2  x)/(sin^3  x +cos^3  x))dx  I′ll post my solution later

$$=\int\frac{\mathrm{sin}^{\mathrm{2}} \:{x}\:\mathrm{cos}^{\mathrm{2}} \:{x}}{\mathrm{sin}^{\mathrm{3}} \:{x}\:+\mathrm{cos}^{\mathrm{3}} \:{x}}{dx} \\ $$$$\mathrm{I}'\mathrm{ll}\:\mathrm{post}\:\mathrm{my}\:\mathrm{solution}\:\mathrm{later} \\ $$

Answered by Frix last updated on 28/Jul/23

∫((sin^2  x cos^2  x)/(sin^3  x +cos^3  x))dx =^(t=sin x +cos x)   =(1/2)∫(((t^2 −1)^2 )/(t(3−t^2 )(√(2−t^2 ))))dt=_( show this in detail]) ^([sorry no time to)   =−(1/2)∫(t/( (√(2−t^2 ))))dt+(1/6)∫(dt/(t(√(2−t^2 ))))−(2/3)∫(t/((t^2 −3)(√(2−t^2 ))))dt=  =((√(2−t^2 ))/2)+((√2)/(12))ln ∣(((√(2−t^2 ))−(√2))/t)∣ −(2/3)tan^(−1)  (√(2−t^2 ))  Now insert t=sin x +cos x =(√2)sin (x+(π/4))

$$\int\frac{\mathrm{sin}^{\mathrm{2}} \:{x}\:\mathrm{cos}^{\mathrm{2}} \:{x}}{\mathrm{sin}^{\mathrm{3}} \:{x}\:+\mathrm{cos}^{\mathrm{3}} \:{x}}{dx}\:\overset{{t}=\mathrm{sin}\:{x}\:+\mathrm{cos}\:{x}} {=} \\ $$$$=\frac{\mathrm{1}}{\mathrm{2}}\int\frac{\left({t}^{\mathrm{2}} −\mathrm{1}\right)^{\mathrm{2}} }{{t}\left(\mathrm{3}−{t}^{\mathrm{2}} \right)\sqrt{\mathrm{2}−{t}^{\mathrm{2}} }}{dt}=_{\left.\:\mathrm{show}\:\mathrm{this}\:\mathrm{in}\:\mathrm{detail}\right]} ^{\left[\mathrm{sorry}\:\mathrm{no}\:\mathrm{time}\:\mathrm{to}\right.} \\ $$$$=−\frac{\mathrm{1}}{\mathrm{2}}\int\frac{{t}}{\:\sqrt{\mathrm{2}−{t}^{\mathrm{2}} }}{dt}+\frac{\mathrm{1}}{\mathrm{6}}\int\frac{{dt}}{{t}\sqrt{\mathrm{2}−{t}^{\mathrm{2}} }}−\frac{\mathrm{2}}{\mathrm{3}}\int\frac{{t}}{\left({t}^{\mathrm{2}} −\mathrm{3}\right)\sqrt{\mathrm{2}−{t}^{\mathrm{2}} }}{dt}= \\ $$$$=\frac{\sqrt{\mathrm{2}−{t}^{\mathrm{2}} }}{\mathrm{2}}+\frac{\sqrt{\mathrm{2}}}{\mathrm{12}}\mathrm{ln}\:\mid\frac{\sqrt{\mathrm{2}−{t}^{\mathrm{2}} }−\sqrt{\mathrm{2}}}{{t}}\mid\:−\frac{\mathrm{2}}{\mathrm{3}}\mathrm{tan}^{−\mathrm{1}} \:\sqrt{\mathrm{2}−{t}^{\mathrm{2}} } \\ $$$$\mathrm{Now}\:\mathrm{insert}\:{t}=\mathrm{sin}\:{x}\:+\mathrm{cos}\:{x}\:=\sqrt{\mathrm{2}}\mathrm{sin}\:\left({x}+\frac{\pi}{\mathrm{4}}\right) \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com